Jalaukavacharana (Medicinal Leech Therapy) and Jatyadi Ghrita in Dushta Vrana w.s.r to Diabetic Foot Ulcer (AYUSHDHARA, 2024)
Ayurveda describes a variety of therapeutic skills, including medicinal, surgical and parasurgical procedures. Jalaukaavacharna is a parasurgical procedure, focuses on removing contaminated blood to treat various conditions. Sushruta Samhita has devoted an entire chapter for the description of Jalauka and Jalaukavacharna in Sutra Sthana 13th Adhyaya and also described Dushta Vrana in Vranasravavigyaniya Adhyaya. The leeches draw out blood while simultaneously secreting substances that are considered beneficial for healing according to Ayurvedic principles. A 60 years old female patient freshly diagnosed with Type 2DM came to RGGPG Ayurvedic college and hospital, Paprola, Himachal Pradesh, with complaints of swelling over right greater toe with purulent discharge and foul smell since two month. After debridement, leech therapy followed by dressing with Jatyadi Ghrita done for three month, twice a week for first month, once a week for second month then after 15 days for next month. Limb elevation and strict diabetic management was advised.